1997
DOI: 10.1007/bf02436974
|View full text |Cite
|
Sign up to set email alerts
|

Planar ZrO2 waveguides prepared by the sol-gel process: Structural and optical properties

Abstract: Abstract. ZrO2 waveguides are prepared by the sol-gel process from a solution containing zirconium n-propoxide and acetylacetone in propanol-2. Structural characterizations are investigated for different annealing temperatures using suitable techniques including Waveguide Raman Spectroscopy, Electron Microscopy and Atomic Force Microscopy. Films are amorphous at 300~ and the pure ZrO2 tetragonal crystalline phase appears beyond 400~ Crystallized films present a dense, uniform and polycrystalline structure made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 9 publications
(9 reference statements)
2
21
0
1
Order By: Relevance
“…Similar results on the increase of optical losses with the annealing temperature were already reported on sol-gel ZrO 2 [25,32] and TiO 2 [33] films. For the former, Ehrhart et al [32] reported that in order to obtain ZrO 2 thin films with a high refractive index (n = 1.96) and low optical losses (0.29 dB/cm), the best heat-treatment corresponds to an annealing at 400 °C, thus preserving an amorphous phase, while optical losses increase at a temperature of 450 °C when the crystallization into a metastable tetragonal phase appears; Urlacher et al [25] also found that ZrO 2 optical losses increase when the annealing temperature and film crystallinity increase: they obtained 0.8 and 2.5 dB/cm as attenuation coefficients for the amorphous film heat treated at 300 °C and the crystallized film annealed at 600 °C, respectively. For the latter, Bahtat et al [33] reported that at lower temperatures (450 °C), the films' structure consists of a mixture of amorphous TiO 2 and anatase nanocrystals and its surface is smooth.…”
Section: Optical Characterizationssupporting
confidence: 87%
See 2 more Smart Citations
“…Similar results on the increase of optical losses with the annealing temperature were already reported on sol-gel ZrO 2 [25,32] and TiO 2 [33] films. For the former, Ehrhart et al [32] reported that in order to obtain ZrO 2 thin films with a high refractive index (n = 1.96) and low optical losses (0.29 dB/cm), the best heat-treatment corresponds to an annealing at 400 °C, thus preserving an amorphous phase, while optical losses increase at a temperature of 450 °C when the crystallization into a metastable tetragonal phase appears; Urlacher et al [25] also found that ZrO 2 optical losses increase when the annealing temperature and film crystallinity increase: they obtained 0.8 and 2.5 dB/cm as attenuation coefficients for the amorphous film heat treated at 300 °C and the crystallized film annealed at 600 °C, respectively. For the latter, Bahtat et al [33] reported that at lower temperatures (450 °C), the films' structure consists of a mixture of amorphous TiO 2 and anatase nanocrystals and its surface is smooth.…”
Section: Optical Characterizationssupporting
confidence: 87%
“…Our results and observations agree with the work of Mechiakh et al [24] who reported that the RMS value was found to increase from 0.617 to 3.713 nm for sol-gel TiO 2 thin films annealed at 350 and 450 °C, respectively; and that the increase in the roughness is due to the increase in the grain size. Similarly, Urlacher et al [25] found, in the case of sol-gel ZrO 2 waveguides, that the amorphous film exhibits a smoother surface than the crystallized one, and the RMS varies from 0.2 to 2.1 nm, when increasing temperature from 300 up to 600 °C. From their analysis, this result is mainly due to crystallite growth when increasing temperature.…”
Section: Morphological Characterizationsmentioning
confidence: 74%
See 1 more Smart Citation
“…Most hybrid materials reported in the literature are based on ZrO 2 and TiO 2 metal oxides [12][13][14][15]. However, though these metal oxides give rise to hybrid materials with excellent optical properties, they are generally obtained after annealing at high temperature (>400°C) [11,12], which is incompatible with many device fabrication processes.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial sintered zirconia is compared with zirconia thin films obtained from the sol-gel process (35). As demonstrated in Ref.…”
Section: Preliminary Study: Influence Of Roughness On Contact Anglementioning
confidence: 99%